Enhancing mechanical properties of copper matrix composite by adding SiO2 quantum dots reinforcement. (January 2022) - Tong, Wanzhe; Fang, Dong; Bao, Chongxi; Tan, Songlin; Liu, Yichun; Li, Fengxian; You, Xin; Tao, Jingmei; Bao, Rui; Li, Caiju; Yi, Jianhong
Abstract: Silica/Cu composites generally fail to achieve the high strength due to the weak interfacial bonding between SiO2 and Cu. In the current work, the first use of silica quantum dots (SiO2 QDs) as a copper-based composite reinforcement. Silicon quantum dots (Si QDs) and copper acetate are employed as raw materials for spray pyrolysis to obtain an interconnected structure of SiO2 QDs/Cu2 O, which achieve well-dispersion of the reinforcement and good interface combination in one step. The SiO2 QDs/Cu2 O composite block is obtained by ball milling, hydrogen reduction, and SPS sintering. Micro interface structure and strengthening mechanism of the composites are investigated and presented in detail. Microstructural analysis discovers the Cu2 O transition layer between SiO2 QDs and Cu matrix and well-dispersed SiO2 QDs in the Cu matrix. The good bonding of grain interface can significantly enhance the mechanical properties. The 1.2 wt% SiO2 QDs/Cu composite block exhibits an excellent ultimate tensile strength of 456.63 MPa, which is 101.68% higher than that of unreinforced Cu (227.39 MPa). Furthermore, the composite block maintains the high conductivity (83.27% IACS) and elongation (8.86%). Moreover, this work can promote the development of Cu matrix composites using ceramic reinforcement with an improved interface bonding. Highlights: The SiO2 QDs as a copper-based composite reinforcement is firstly presented. Good dispersion of the reinforcement in the matrix and strong interface combination are obtained by spray pyrolysis method. The composite compact has achieved good mechanical properties and high conductivity.